Characterization of lipid extracts from the Hermetia illucens larvae and their bioactivities for potential use as pharmaceutical and cosmetic ingredients. Issue 5 (May 2022) - Almeida, Cíntia; Murta, Daniel; Nunes, Rui; Baby, André Rolim; Fernandes, Ângela; Barros, Lillian; Rijo, Patricia; Rosado, Catarina
Abstract: There is an increasingly growing demand for the use of natural and sustainable bioactives in the field of the pharmaceutical and cosmetic industries. The biomass from black soldier fly larvae ( Hermetia illucens ) can be viewed as an innovative source of compounds with high aggregate value and marketing potential due to the sustainable organic matter bioconversion process used as substrate for its development. This insect can be a source of lipid compounds with high added value, mainly due to its high content in fatty acids (FA) with potential applicability in the pharmaceutical and cosmetic industry. In this context, in this work different extraction methods were tested (decoction, microwaves, maceration and ultrasound), using water, acetone, n- hexane as extraction solvents, to evaluate yields of the BSF larvae lipid extracts, as well as their lipid profile, and a preliminary safety screening was conducted. Results show that despite using different extraction techniques and solvents, similar FA composition profiles were obtained. The lauric acid content (C12: 0) is elevated in all the extracts in relation to the other FA, ranging 37%–62%. The contents in palmitic (C16: 0) and oleic (C18: 1n-9) acids, were also high in all applied extraction methods. The omega-6 FA (ω-6 PUFAs), mainly linoleic acid (C18: 2n6c), were also identified in the lipid fraction of BSF larvae biomass, with a content variation between 4.5% and 17.7%, while the omega-3 group, namely α-Linolenic acid (C18: 3n3), presented values between 0.66% and 1.95%. None of the extracts presented toxicity in preliminary tests with the Artemia salina model. Through this study, it was possible to confirm that BSF larvae oil can be obtained by sustainable methods, containing a broad mixture of FA and being highly rich in lauric acid, with a promising skin care applicability. Abstract : Insect; Hermetia illucens ; Lipids; Biomass; Skin.